The effect of axial charge stratification and exhaust gases on combustion ‘development’ in a homogeneous charge compression ignition engine - Hardalupas, Yannis; Aleiferis, Pavlos G.; Taylor, Alexander; Urata, Yasuhiro; Charalambides, Alexandros G. (My University, 2008)
A high-swirl low-compression-ratio, optically accessed engine that was able to produce a stratified charge was used to investigate the differences in homogeneous charge compression ignition (HCCI) combustion and in the propagation of the autoignition front between a non-stratified and a stratified charge. Natural-light images were acquired using a fast camera to visualize HCCI combustion and to quantify the location of autoignition, the apparent ‘propagation speed’ of the autoignition front, and its variations between closed-valve injection timing (leading to a nearly homogeneous charge) and open-valve injection timing (leading to a strongly axially stratified charge), owing to temperature inhomogeneities that were introduced by utilizing a camshaft which allowed 40 per cent internal exhaust gas recirculation (iEGR). Experimental results show that, in the case without exhaust gas recirculation (EGR) and with closed-valve injection timing, autoignition started under the primary intake valve near the cylinder wall, while, in the case without EGR and with open-valve injection timing, autoignition started between the exhaust valve and the secondary intake valve, closer to the centre of the piston. With 40 per cent iEGR and closed-valve injection timing, autoignition started between the exhaust valve and the primary intake valve near the cylinder wall. These differences can be explained by the difference in the location of hot gases due to the injection timing or due to iEGR. Finally, without EGR, a ‘uniform’ autoignition front of HCCI combustion from the original sites of autoignition was observed compared with a more ‘random development’ of the autoignition front with 40 per cent iEGR. Strong local inhomogeneities (possibly a very rich mixture at a low temperature) could be present with 40 per cent iEGR.
Keywords: Axial charge stratification; Exhaust gases; Combustion development; Homogeneous charge compression ignition engine